Bellman–Steffensen type inequalities - Julije Jakšetić; Josip Pečarić; Ksenija Smoljak Kalamir (Journal of Inequalities and Applications, 2018)
Abstract In this paper some Bellman–Steffensen type inequalities are generalized for positive measures. Using sublinearity of a class of convex functions and Jensen’s inequality, nonnormalized versions of Steffensen’s inequality are obtained. Further, linear functionals, from obtained Bellman–Steffensen type inequalities, are produced and their action on families of exponentially convex functions is studied.